PENERAPAN METODE LATIHAN SOAL (RESPONSI) DALAM MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS PADA MATA KULIAH PROGRAM LINEAR - Awatif (Matedukasia, 2023)
One way to improve mathematical communication skills is by applying the method of practice questions (responses). To be able to improve learning outcomes in improving mathematical communication skills, the question practice method is an alternative method that lecturers can use in learning. In this study using action research which was carried out in two cycles and looking at student learning activities related to attendance, activeness and attention in learning. Based on the results of this study, it was stated that the application of the practice questions method could improve the ability to understand mathematical concepts as indicated by the average learning outcomes that increased from cycle I to cycle II. From the data on understanding mathematical concepts, it shows that students' ability to understand a lot of mathematical concepts in applying the method of practice questions is in the medium category in cycle I and cycle II. For student learning activities, data were obtained from observation sheets, which showed that student learning activities also increased from cycle I to cycle II. From the discussion, it can be concluded that the application of the problem practice method (Response) can improve the ability to understand mathematical concepts in mathematics linear program courses. The average learning outcomes in the first cycle using the practice questions method was 77.75, increasing in the second cycle was 75.38 with the same method and the average student had moderate understanding of mathematical concepts